1985
DOI: 10.1002/ijc.2910350609
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of adult T‐cell leukemia‐lymphoma and its familial clustering

Abstract: The yearly incidence of ATLL in the Uwajima district is 6.6 patients per 100,000 inhabitants aged over 40. The yearly morbidity rate from ATLL of persons in this district who are positive for HTLV-antibody and older than 40 is 1 patient per 1,631. Familial occurrence was observed in 9/38 families available for pedigree analyses. Even in the endemic area, the existence of positive HTLV antibody is remarkably high in ATLL families, suggesting that HTLV has been transmitted from generation to generation mainly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Thirteen of them were designed to identify or explain family aggregation, including 10 cross-sectional studies (Kondo et al, 1985; Matsuo et al, 1989; Kayembe et al, 1990; Tajima, 1990; Bhigjee et al, 1995; Iwanaga et al, 1995; Pombo-de-Oliveira et al, 2001; Cabada et al, 2007; Alvarez et al, 2014; Nozuma et al, 2014), two reviews (Manns and Qasba, 1999; Shoeibi et al, 2013), and one cohort study (Iwanaga et al, 2010). The remaining 61 records were either case reports or reports of family clusters that were identified within other epidemiological studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of them were designed to identify or explain family aggregation, including 10 cross-sectional studies (Kondo et al, 1985; Matsuo et al, 1989; Kayembe et al, 1990; Tajima, 1990; Bhigjee et al, 1995; Iwanaga et al, 1995; Pombo-de-Oliveira et al, 2001; Cabada et al, 2007; Alvarez et al, 2014; Nozuma et al, 2014), two reviews (Manns and Qasba, 1999; Shoeibi et al, 2013), and one cohort study (Iwanaga et al, 2010). The remaining 61 records were either case reports or reports of family clusters that were identified within other epidemiological studies.…”
Section: Resultsmentioning
confidence: 99%
“…A series of cross-sectional survey for residents in Uwajima City (population size; 290, 464, HTLV-1-positive rate; 5.4% in men and 8.3% in women) reported that the annual incidence of ATL was estimated to be approximately 6.1 in adults aged over 30 years per 100,000 populations (Kondo et al, 1985, 1987, 1989). In another cross-sectional studies by the use of the regional cancer registry data in Nagasaki prefecture (an endemic area, the population size; 1.56 million), the age-standardized annual incidence rate of ATL (among 100,000 individuals aged 30 or older) was estimated to be 10.5 for men and 6.0 for women during 1985–1995 (Arisawa et al, 2000) and 8.7 for men and 5.5 for women during 1995–2004 (Arisawa et al, 2009).…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…The diagnosis of T-cell lymphoma in two brothers provides further support of the familial pattern of this disease. Two cases each of ATL from five families for a total of 10 cases were reported from the Uwajima district in Japan (Kondo et al, 1985). Another study in the Nagasaki district identified 16 families, each with two or more cases of ATL, usually including parent-child or sibling relationships (Ichimaru et al, 1986).…”
Section: Discussionmentioning
confidence: 99%